3‐D printed waveguide attenuators operating at ka‐band (26.5‐40 GHz). Issue 3 (25th September 2020) - Wang, Yi; Guo, Cheng; Shang, Xiaobang; Wu, Wen
Abstract: In this article, two Ka‐band (26.5‐40 GHz) waveguide attenuators designed for three‐dimensional (3‐D) metal printing are presented. These designs are based on long waveguides with elliptical cross‐sections, so that the waveguide structure can be self‐supported during printing. Bended waveguide and helical waveguide are utilized by the two attenuators, respectively, to achieve reduced overall sizes. The attenuations are fixed, however, these can be altered by varying the length/height of waveguides. The limitation of 3‐D metal printing process on surface roughness is also used to provide attenuation. Therefore, the proposed attenuators can cope with printing process with relatively poor surface finish. The prototype designs are fabricated using a metallic selective laser melting (SLM) process and are measured to have good electrical performance across the full waveguide band. The measured attenuation values are in the range of 3.7 to 6.3 dB for the bended waveguide attenuator and 4.3 to 6.3 dB for the helical waveguide attenuator. Both attenuators are measured to have a good return loss (S11 < −20 dB) across the whole Ka‐band. This demonstrates that 3‐D metal printed attenuators could be an attractive alternative to the conventional designs based on absorbing materials, particularly for applications demanding high powers.